Indentation Size Effect Model of Ti6Al4V Alloy by Combining the Macroscopic Power‐Law Constitutive Relation and Strain Gradient Theory. Issue 9 (30th March 2022) - Cui, Weiling; Qiu, Ji; Wang, Hefeng; Su, Buyun
Abstract : Indentation size effect (ISE) is a critical feature for investigating the local properties of materials using the indentation test method. Although there are numerous works on the indentation response, there is a lack of data in the literature on the association between nanoindentation and uniaxial compression. Herein this study, uniaxial compression tests combined with Digital Image Correlation Technique are conducted on Ti6Al4V alloy with a focus on investigating the elastic–plastic properties and obtaining the accurately constitutive relation. Then, an ISE model of Ti6Al4V is established based on this constitutive relation and strain gradient theory. Indentation hardness, predicted by this proposed model, agrees well with the measurement by nanoindentation experimental techniques. This model can be used to bridge the gap between the uniaxial stress–strain and the depth‐dependent hardness, and clarifies the effect of the strain hardening on indentation hardness. The significance of this model is that it provides a direct and reasonable theory foundation to investigate ISE by uniaxial compression, and promotes the potential application of nanoindentation. Abstract : Uniaxial compression tests combined with Digital Image Correlation Technique are conducted on Ti6Al4V with a focus on investigating the elastic–plastic properties and obtaining the accurately constitutive relation. Then, an ISE model is established based on this constitutive relation and strain gradient theory. This model can be used to bridge the gap between the uniaxial compression and nanoindentation.